An Empirical Research about Xinjiang Minority College Students’ Value Recognition in Inner-Mainland's Universities of China - Zhu, Hai-Long (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2016)
In order to understand value recognition deeply, the research was taken to 1128 Xingjiang minority college students in inner-mainland 36 universities of China by the questionnaire with five dimensions which political value, moral value, cultural psychology, language stress and environmental stress. The result showed that there was an order tendency in their values, in order, cultural psychology, moral values, political values, language stress and environmental stress. At the same time, there are gander differences. Male and female college students do not exist significant differences in cultural psychology and moral value dimensions. But the differences being in the political values, language stress and environmental stress. Xinjiang minority college students are fundamentally the same as Han nationality students in political values and moral values, but obvious differences in cultural psychology, language stress and environmental stress.
Keywords: Xingjiang minority college students; inner-mainland; universities; value; recognition